Prevalence Of Intestinal Parasites Infestation in Surat City of South Gujarat: A Hospital Based Study - Patel, Mandakini M; Patel, Prashant R; Gamit, Bhavna; Modi, Jigna; Padsala, Suresh (National Journal of Community Medicine, 2014)
Introduction: Pathological intestinal infection by parasites causes malnutrition, decreased immunity, protein loss, mucosal loss in infants and lymphatic leakage and local hemorrhage. In developing countries parasitic infections are more prevalent than bacterial infection and causes significant morbidities. This study was undertaken to comprehend the prevalence of parasitic infections. Material and Methods: Both outdoor as well as indoor patients taking treatment in New Civil Hospital, Surat were included in present study. Naked eye physical examination, microscopic examination was carried out. Parasites were identified in the received stool samples. All data were entered into excel spreadsheet 2007. The percentages of the parasites presents were calculated to find out prevalence of parasite infestations and data were analyzed for interpretation. Results: Total 1170 samples were included in present study, out of which 65 (5.56%) were positive either for protozoal or helminthic infections. Helminth Infestation found in 45 (65.21%) cases while Protozoal infestation found in 24 (34.79%) cases while 4 (6.15%) cases showed mixed infection of helminth and protozoa. Children under 18 years of age (6.23%) were more commonly affected than adults (4.92%). The most common parasite encountered in present study was Giardia Lamblia (28.99%) followed by Hymenolepys Nana (20.29%). Conclusion: The present study showed low prevalence of intestinal parasites might be due to improved sanitary practices, personal hygiene, safe drinking water and health awareness. Children showed higher prevalence for intestinal parasites in comparison with adults. Prevalence of helminthes was higher than protozoa in present study.